Human dose-escalation study of PET imaging CD8+ T-cell infiltration in solid malignancies with 68GaGa -NODAGA-SNA006 - Wang, Yan; Zheng, Meng; Zhao, Jun; Wang, Chao; Zhao, Shandong; Bian, Yicong; Dai, Na; Zheng, Yushuang; Sang, Shibiao; Guo, Linchuan; Huang, Chenrong; Zhang, Hua; et al. (European journal of nuclear medicine and molecular imaging, 2024)
A noninvasive method for evaluating the infiltration of CD8+ T cells in tumors is urgently needed to monitor the response to immunotherapy. This study investigated the performance of a [68Ga]Ga-NODAGA-SNA006 in positron emission tomography (PET) imaging of CD8+ T cells in patients with solid malignancies.PURPOSEA noninvasive method for evaluating the infiltration of CD8+ T cells in tumors is urgently needed to monitor the response to immunotherapy. This study investigated the performance of a [68Ga]Ga-NODAGA-SNA006 in positron emission tomography (PET) imaging of CD8+ T cells in patients with solid malignancies.This human dose-escalation PET imaging study involved eleven patients (lung cancer, 8; gastric carcinoma, 1; esophageal carcinoma, 2). Approximately 150 MBq of [68Ga]Ga-NODAGA-SNA006 with varying nanobody masses (100 µg, 300 µg, 500 µg, 800 µg) was administered, and PET/computed tomography (CT) scans were performed at 15-30, 60-90 and 120 min postinjection (p.i.). Data regarding biodistribution, pharmacokinetics and radiation dosimetry were evaluated. CD8+ T-cell infiltration in biopsy samples was also measured via immunohistochemistry (IHC) for correlation analysis with the tumor uptake of [68Ga]Ga-NODAGA-SNA006 PET.METHODSThis human dose-escalation PET imaging study involved eleven patients (lung cancer, 8; gastric carcinoma, 1; esophageal carcinoma, 2). Approximately 150 MBq of [68Ga]Ga-NODAGA-SNA006 with varying nanobody masses (100 µg, 300 µg, 500 µg, 800 µg) was administered, and PET/computed tomography (CT) scans were performed at 15-30, 60-90 and 120 min postinjection (p.i.). Data regarding biodistribution, pharmacokinetics and radiation dosimetry were evaluated. CD8+ T-cell infiltration in biopsy samples was also measured via immunohistochemistry (IHC) for correlation analysis with the tumor uptake of [68Ga]Ga-NODAGA-SNA006 PET.[68Ga]Ga-NODAGA-SNA006 was well tolerated by all eleven subjects. The highest radioactive uptake was observed in the spleen, followed by the kidneys and bladder. Liver uptake decreased with increasing nanobody mass. Rapid clearance (t1/2<30 min) of [68Ga]Ga-NODAGA-SNA006 from whole blood and serum was observed. Furthermore, 68Ga uptake in tumors (SUVmean) exhibited a linear relationship with CD8+ T-cell infiltration in biopsy samples (R2 = 0.757, p = 0.011), suggesting that the tumor uptake of [68Ga]Ga-NODAGA-SNA006 may represent the degree of CD8+ T-cell infiltration in the tumor.RESULTS[68Ga]Ga-NODAGA-SNA006 was well tolerated by all eleven subjects. The highest radioactive uptake was observed in the spleen, followed by the kidneys and bladder. Liver uptake decreased with increasing nanobody mass. Rapid clearance (t1/2<30 min) of [68Ga]Ga-NODAGA-SNA006 from whole blood and serum was observed. Furthermore, 68Ga uptake in tumors (SUVmean) exhibited a linear relationship with CD8+ T-cell infiltration in biopsy samples (R2 = 0.757, p = 0.011), suggesting that the tumor uptake of [68Ga]Ga-NODAGA-SNA006 may represent the degree of CD8+ T-cell infiltration in the tumor.The use of [68Ga]Ga-NODAGA-SNA006 is safe, feasible, and well tolerated. [68Ga]Ga-NONAGA-SNA006 PET imaging can accurately detect CD8 expression inside tumors with favorable pharmacokinetics, thus providing a feasible method for noninvasive quantitative assessment of CD8+ T-cell tumor infiltration and monitoring the response to immunotherapy.CONCLUSIONThe use of [68Ga]Ga-NODAGA-SNA006 is safe, feasible, and well tolerated. [68Ga]Ga-NONAGA-SNA006 PET imaging can accurately detect CD8 expression inside tumors with favorable pharmacokinetics, thus providing a feasible method for noninvasive quantitative assessment of CD8+ T-cell tumor infiltration and monitoring the response to immunotherapy.NCT05126927 (19 November 2021, retrospectively registered).TRIAL REGISTRATIONNCT05126927 (19 November 2021, retrospectively registered).